An integrated fuzzy approach to students' assessment / Badrul Hisham Abdullah - Abdullah, Badrul Hisham (2006)
Assessment is a process of collecting data for the purpose of making decisions about individuals or groups. In education, instructors assess students by giving grades to express the overall performance of the students. The main objective of this study is to improvise the existing fuzzy approach in assessing students’ performance. This study focuses on two types of assessments namely students’ answer scripts assessment and students’ group assessment. In the students’ answer scripts assessment the trapezoidal fuzzy number is used to represent the standard satisfaction level for the grading scales and the students’ fuzzy scores. The center points of both standard satisfaction levels and the fuzzy score is calculated using the center of gravity method. The minimum distance between the fuzzy score and the standard satisfaction level will determine the linguistic term that best represent the students’ performance. In the students’ group assessment instructors as well as students are involved in selecting and determining the assessment criteria. The pair-wise comparison technique based on fuzzy scales is used to find the relative strength between each criterion. The weights of selected criteria are represented by the normalized fuzzy eigenvectors. The fuzzy relation composition method is employed in order to combine the instructor and students’ evaluation, which finally will give the overall students’ group performance. Both the answer scripts assessment and group assessment processes can be easily performed with the aid of fuzzy assessment sheet. This integrated fuzzy approach provides additional information on students’ performance and can be used as an option for instructors to assess students’ performance.